Long-term results comparison after anterior cervical discectomy with BGS-7 spacer (NOVOMAX®-C) and allograft spacer: A prospective observational study - Ryu, Seungjun; Ryu, Dal-Sung; Kim, Keun-Su (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: In an anterior cervical discectomy and fusion (ACDF), various types of graft materials including autograft, allograft, and synthetic graft have been used to achieve adequate spinal fusion. Allograft spacer is mainly used in cervical fusion, especially in the anterior approach. The synthetic bone graft material BGS-7(CaO-SiO2-P2O5-B2O3, bioactive Glass-Ceramics) can bind with surrounding bone tissue by forming a hydroxyapatite layer bone bridge, leading to faster graft osseointegration. This study was conducted to compare long-term clinical outcome of BGS-7 spacer and allograft spacer for anterior cervical discectomy and fusion surgery. Materials and Methods: From September 2014 to December 2016, Consecutive anterior cervical discectomy and fusion surgeries using a BGS-7 spacer (N = 18) and Allograft spacer (N = 26) were compared for postoperative clinical outcomes. Radiologic assessments were performed, and Instrumental failure, including breakage, cage migration, subsidence were observed and Fusion status were analyzed. Finite element analysis was performed for simulating mechanical stress between the vertebral body and implant. Clinical outcomes were evaluated using neck VAS, NDI, and JOA on the patient’s final follow-up visits. Results: Among the 44 patients who underwent an anterior cervical discectomy and fusion surgery using the BGS-7 spacer and Allograft spacer, there were 30 men and 14 women. The average age at the operation was 47.69 ± 10.49 in allograft spacer and 51.67 ± 11.03 in BGS-7 spacer. The mean follow-up period was 89.18 ± 5.44 months. Twenty three (88.46%) patients in allograft spacer and 20(100%) patients in BGS-7 spacer were demonstrated radiologic evidence of interbody fusion in last OPD, which accounts for fusion grade 4 or 5. Peak stresses were 343.85 MPa in allograft spacer, and 132.55 MPa in BGS-7 spacer. Long-term clinical outcomes including neck VAS, NDI, and JOA didn’t show statistical differences between the two groups. There were no adverse events related to the BGS-7 spacer.10.3389/fbioe.2023.110046. Conclusion: The BGS-7 spacer demonstrated reliability as a spacer in anterior cervical discectomy and fusionF surgery without instrumental failure. Early stabilization with a bony bridge formation was observed at the intermediate follow-up period, and the long-term clinical outcome was favorable at more than 60 months after surgery without any adverse events. Thus, the BGS-7 spacer is a safe and effective alternative to the allograft spacer in anterior cervical discectomy and fusion surgery.